Characterization of Porphyromonas gingivalis sialidase and disruption of its role in host–pathogen interactions. Issue 11 (13th September 2019) - Frey, Andrew M.; Satur, Marianne J.; Phansopa, Chatchawal; Honma, Kiyonobu; Urbanowicz, Paulina A.; Spencer, Daniel I. R.; Pratten, Jonathan; Bradshaw, David; Sharma, Ashu; Stafford, Graham
Abstract : Key to onset and progression of periodontitis is a complex relationship between oral bacteria and the host. The organisms most associated with severe periodontitis are the periodontal pathogens of the red complex: Tannerella forsythia, Treponema denticola and Porphyromonas gingivalis . These organisms express sialidases, which cleave sialic acid from host glycoproteins, and contribute to disease through various mechanisms. Here, we expressed and purified recombinant P. gingivalis sialidase SiaPG (PG_0352) and characterized its activity on a number of substrates, including host sialoglycoproteins and highlighting the inability to cleave diacetylated sialic acids – a phenomenon overcome by the NanS sialate-esterase from T. forsythia . Indeed SiaPG required NanS to maximize sialic acid harvesting from heavily O-acetylated substrates such as bovine salivary mucin, hinting at the possibility of interspecies cooperation in sialic acid release from host sources by these members of the oral microbiota. Activity of SiaPG and P. gingivalis was inhibited using the commercially available chemotherapeutic zanamivir, indicating its potential as a virulence inhibitor, which also inhibited sialic acid release from mucin, and was capable of inhibiting biofilm formation of P. gingivalis on oral glycoprotein sources. Zanamivir also inhibited attachment and invasion of oral epithelial cells by P. gingivalis and other periodontal pathogens, both in monospecies but also in multispecies infection experiments, indicating potential to suppress host–pathogen interactions of a mixed microbial community. This study broadens our understanding of the multifarious roles of bacterial sialidases in virulence, and indicates that their inhibition with chemotherapeutics could be a promising strategy for periodontitis therapy.